A note on classical adjoint commuting linear maps of tensor products of matrices. Issue 4 (2nd April 2016) - Chooi, Wai Leong; Kwa, Kiam Heong; Lau, Jinting
Abstract : Let be the algebra of matrices over a field with at least three elements. Inspired by linear preserver problems related to quantum information science, we characterize classical adjoint commuting linear maps, i.e. linear maps such that with, that preserve decomposable tensors of . Some examples are given to distinguish the study of classical adjoint commuting linear maps of tensor products of matrices from those found in the study of classical adjoint commuting linear maps on matrix spaces.